ANALISIS EFEKTIFITAS KINERJA KEUANGAN DINAS PENDAPATAN DAERAH (DISPENDA) KOTA MAKASSAR - Abdul Rauf (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
Financial performance is a picture of financial condition in a given period either in relation to aspects of fund raising and distributing funds that are usually measured by indicators of capital adequacy, liquidity, and profitability. Profitability assessment aspect to determine the ability to create profits, which are certainly important for the owners. With good financial performance will ultimately affect both the internal and for external parties.